Diversion Program Imposed on Juvenile Offenders of Philippines And Indonesia: A Comparative Study - Ika Dewi Sartika Saimima; Johndex Emanuel S. Villarico; Hipolito B. Quillip Jr (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2024)
This study aims to compare find out the similarities and differences of the Diversion Programs imposed on Juvenile Offenders in Philippines and Indonesia. The researchers utilized the descriptive comparative analysis in conducting this study. This research is conducted using secondary data and using the Republic Act 9344 of the Philippines and the Law No. 11 of 2012 of Indonesia as sources. The researcher has the following criteria in comparing if there are provisions under the Republic Act 9344 of the Philippines and the Law No.11 of 2012 of Indonesia that provides for the (a) Factor in Determining the Diversion Program Imposed on the CICL (b) Classification of Diversion Program Imposed on Juvenile Offender and (c) Ensuring the Confidentiality of the Information Regarding the CICL. The researchers found out six (6) similar provisions and four (4) different provisions that pertains to the Factor in Determining the Diversion Program Imposed on the CICL, four (4) similar provisions and two (2) different provisions that pertains to different Classification of Diversion Program Imposed on Juvenile Offender and one similar provision that pertains to Ensuring the Confidentiality of the Information Regarding CICL.